Spatial comparison and temporal evolution of two marine iron-rich microbial mats from the Lucky Strike Hydrothermal Field, related to environmental variations - Astorch-Cardona, Aina; Guerre, Mathilde; Dolla, Alain; Chavagnac, Valérie; Rommevaux, Céline (Frontiers in Marine Science, 2023)
In hydrothermal environments, diffuse fluids emanations provide optimal conditions for the development of iron-rich microbial mats. Here, we present a unique spatial and temporal study of phylogenetic and chemical data from this type of mats and their associated hydrothermal fluids from two sites of the Lucky Strike Hydrothermal Field (EMSO-Azores deep-sea observatory), collected annually from 2016 to 2020. Our metabarcoding analyses reveal a completely different microbial community at each site, linked to the distinctive chemical composition of the diffuse fluids nourishing the mats. Capelinhos site is dominated by microorganisms with metabolisms related to iron, methane, and reduced sulphur compounds, coming from hydrothermal fluids, while North Tour Eiffel site presents higher abundances of microorganisms with metabolisms related to nitrogen, organic and oxidized sulphur compounds, coming from seawater. We present for the first time the yearly evolution of these mats over a five-year period. This analysis reveals similar variations of the microbial communities over time at both sites, indicating a regional Lucky Strike influence on the temporal scale. We also highlight more diversified microbial communities at both sites in 2016, pointing out the occurrence of a geological event that could have affected them during this specific year. Except for this year, our study shows that the communities of iron-rich microbial mats remain stable over time at both sites.